2009
DOI: 10.1111/j.1526-4637.2009.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Transcranial Magnetic Stimulation in Patients with Fibromyalgia and Major Depression

Abstract: With the methodology used in this study, patients with fibromyalgia and major depression who received real magnetic stimulation did not present significant differences in symptoms with respect to those who received sham magnetic stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 26 publications
2
48
1
2
Order By: Relevance
“…Although the data in the literature are not homogeneous, both HF and LF protocols seem to have similar response rates (Brunoni et al, 2009;Carretero et al, 2009;Eche et al, 2012;Fitzgerald et al, 2009;Pallanti et al, 2010;Schutter, 2010). We provide here further indication of the value of LF-rTMS in a large sample with MDD, including elderly people, with an efficacy similar to that of HF-TMS, as reported by Milev et al (2009).…”
Section: Discussionsupporting
confidence: 74%
“…Although the data in the literature are not homogeneous, both HF and LF protocols seem to have similar response rates (Brunoni et al, 2009;Carretero et al, 2009;Eche et al, 2012;Fitzgerald et al, 2009;Pallanti et al, 2010;Schutter, 2010). We provide here further indication of the value of LF-rTMS in a large sample with MDD, including elderly people, with an efficacy similar to that of HF-TMS, as reported by Milev et al (2009).…”
Section: Discussionsupporting
confidence: 74%
“…There were also studies that used low frequency for pain relief in FM. A study that had four patients found pain improvement, but in a second study, no difference was reported between the sham and real treatment groups (31,32). However, in both studies, LF-rTMS stimulation was applied to the prefrontal cortex area.…”
Section: Discussionmentioning
confidence: 99%
“…94,95 rTMS of the M1 and dorsolateral prefrontal cortex has been shown to be efficacious in reducing pain associated with fibromyalgia in various studies. 35,44,[96][97][98][99][100] Sampson and colleagues 97 reported the efficacy of low-frequency (1-Hz) rTMS of the right DLPFC in 4 patients with depression and fibromyalgia. Average pain reduced from a pretreatment level of 8.2 (Likert scale) to 1.5 after rTMS and 2 patients reported complete resolution of pain in this study.…”
Section: Rtms Of M1 For Chronic Painmentioning
confidence: 97%